PLANNING FOR IMPROVEMENT OF KRIAN ROAD -KEMANGSEN - Purnomo, Dwi; Oetomo, Wateno; Muhammadun, Haris (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2022)
Pavement improvement on Kemangsen road is necessary to repair the old concrete pavement, which is corrugated/subside so that it hinders the movement of passengers and goods. Therefore, the improvement of road pavement must comply with predetermined standards. The general objective of the Road Pavement Improvement activity on the Kemangsen road section is to make a technical road plan that follows the heavy vehicle traffic that passes through the road section. The specific objective of the Road Pavement Improvement activity on the Kemangsen road section is to analyze the structure of the old concrete pavement and to plan for field survey-type road pavement improvements to be carried out in this Preliminary Survey is a visual inspection. The Krian–Kemangsen Road was the location where the study took place. Traffic analysis is very decisive in obtaining the optimal corridor and the priority for implementing its development. Land use in the planned alignment area is strongly influenced by the development of the surrounding area, which is expected to develop into a residential area. The consultant will carefully investigate the physical condition of the land because it greatly influences the implementation aspects of Road construction. The selection of construction methods and types of construction is expected to support and follow the natural characteristics around the location of the development plan so that the planning is more economical and environmentally friendly.